Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/c9nr08113e
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion layer influence on controlling the local temperature in plasmonic gold nanoholes

Abstract: The gold adhesion layer can have a dramatic impact on the thermal response of plasmonic structures, offering new ways to promote or avoid the temperature increase in plasmonics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…Plasmonics is bound to absorption losses into the metal, which induce a local temperature gradient around the nanostructure. [44][45][46][47][48] This temperature gradient then exerts a thermophoretic force on the nano-object as a consequence of the Ludwig-Soret effect. [49][50][51][52] The main physical principle here is that the thermal gradient generates an interfacial fluid flow at the nano-object surface, which in turn moves the object across the solution.…”
mentioning
confidence: 99%
“…Plasmonics is bound to absorption losses into the metal, which induce a local temperature gradient around the nanostructure. [44][45][46][47][48] This temperature gradient then exerts a thermophoretic force on the nano-object as a consequence of the Ludwig-Soret effect. [49][50][51][52] The main physical principle here is that the thermal gradient generates an interfacial fluid flow at the nano-object surface, which in turn moves the object across the solution.…”
mentioning
confidence: 99%
“…Recently, Wenger et al quantified the temperature rise caused by trapped beams focused on single/double gold nanoholes. They found that the temperature gain was largely controlled by ohmic losses of the metal layer, independent of the aperture parameters or laser polarization 313,314 . In the following, many other works also discussed the temperature in nanoholes [315][316][317] .…”
Section: Sensing and Imagingmentioning
confidence: 99%
“…With 𝑅 = 14 nm and ℎ = 15 nm, the 6𝜋𝜂𝑅 term in the drag coefficient is increased by a factor 2.5, which appears similar to what was used in a previous study 7 . For a more accurate measurement, we also take into account the temperature dependence of the water viscosity 𝜂 using the Vogel equation 36 and our previous calibration of the temperature inside DNH structures as a function of the infrared laser power 37,38 .…”
Section: Theorymentioning
confidence: 99%